Sosialisasi Digitalisasi Sebagai Pendorong Peningkatan Pelayanan Publik Dan Inovasi Bisnis UMKM Di Desa Dasan Tereng - Baiq Ertin Helmida; Baiq Kisnawati; Lalu Mimbar; Satriawan; Faizatul Fajariah; Rizaldi Gilang Ramadan; Ahmad Hasbullah (Valid Jurnal Pengabdian, 2026)
Community Service activities in the form of outreach are a strategic step to encourage the use of digitalization in public services and MSME innovation in Dasan Tereng Village. The objectives of this activity are as follows: 1) To increase the understanding of village officials in utilizing digital technology for public services and the optimal use of other social media; 2) To increase the understanding of MSMEs in utilizing digital technology for business activities and encourage MSME business innovation through online marketing; 3) To encourage collaboration between universities, village governments, and business actors in implementing digitalization programs at the local level. The method used was preparation, namely conducting surveys, identifying problems, implementing activities, and finally, evaluating them. The results of this activity were: 1) Increased understanding of village officials in utilizing digital technology for public services (e.g., online administration, village websites, and service applications) and the optimal use of other social media; 2) Increased understanding of MSMEs in utilizing digital technology for business activities (e-commerce and other business applications) and encouraged MSME business innovation through online marketing (internet and digital technology); 3) Establishing a sustainable partnership between STIE AMM, village government, and MSME actors in developing the digital economy.